AFFECTIVE FILTER TERHADAP PENGAJARAN BAHASA KEDUA (BAHASA ARAB) - Alwazir Abdusshomad (Politeknik Penerbangan Indonesia Curug, 2012)
Language has an important function in human’s life. By using language, human can exchange their opinion and information all around the world. Arab language, specially, is an international language which is learnt by Indonesian. To learn Arab or other languages in which the previous language is mastered is known as second language acquisition. In second language acquisition, there’s an affective filter hypothesis which is designed by Krashen. Affective filter block the learners’ input so its function as a mental block for the second language learners. This journal introduces the concept of affective filter which has four factors. By analyzing this topic, second language teachers can find a better way to conduct their teaching.